The Field Education: a study on the conditions of schools in Agrarian Reform settlements - Machado, Vitor [UNESP]; Tsuchiya, Amanda Matheus [UNESP] (Univ Nove Julho, 2021)
Field Education arises in Brazil as a result of the struggle process of rural social movements, especially the Settled Rural Workers Movement (MST). Thus, this work aims to demonstrate that despite public policies for rural education, major advances, the current reality of rural schools reveals the existence of a chasm between such policies and the educational challenges to be faced by schools in rural areas. Analyzes carried out in the light of the 2018 School Education Census (BRASIL, 2019) reveal the great precariousness of the infrastructure of these schools and the closing of a significant number of them in recent years. All these problems pointed out, as a result of the abandonment of our governors, cause great difficulties in the teaching and learning process of rural students and also contribute to a significant number of children and young people in rural areas remaining out of school.
Keywords: field education; field school; rural education